The Cult of Spontaneity: Finnish-Canadian Bushworkers and the Industrial Workers of the World in Northern Ontario, 1919-1934 - Campbell, J. (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1998)
Abstract In THE 1920s and early 1930s the Industrial Workers of the World were a force to be reckoned with among Finnish bushworkers in northern Ontario. Although the Lumber Workers Industrial Union no. 120, affiliated with the Industrial Workers of the World, was smaller than its rival, the Lumber Workers Industrial Union of Canada, affiliated with the Communist Party, the Wobbly union played a major role in bushworker strikes in the mid-1920s and early 1930s. Committed to anti-authoritarianism, decentralization, and rank-and-file initiative, Finnish Wobbly bushworkers were part of an ethnic-based working-class culture in which the economic struggles of the bushworkers were made possible by the tireless work of Finnish Wobbly women, who were the backbone of Wobbly social, cultural, and organizational life in urban centres like Port Arthur. In a 20th century dominated by bureaucracy, legality, and state-directed social programs, the Finnish Wobblies of northern Ontario leave a legacy of dedication to self-education and self-activity in an age so often identified with the demise of the Wobblies and the victory of mass culture.